Effect of different resin luting cements on the marginal fit of lithium disilicate pressed crowns - Mounajjed, Radek; Salinas, Thomas J; Ingr, Tomas; Azar, Basel (The Journal of prosthetic dentistry, 2018)
STATEMENT OF PROBLEM: The vertical marginal discrepancy of restorations can increase upon cementation, and poor marginal fit can lead to cement dissolution, marginal discoloration, microleakage, and secondary caries. The amount of increase is related to the type of luting cement used, but how lithium disilicate pressed crowns are affected by different resin cements is unclear. PURPOSE: The purpose of this in vitro study was to compare the effect of using different resin luting cements on the vertical marginal discrepancy of lithium disilicate pressed crowns. MATERIAL AND METHODS: A total of 18 intact extracted mandibular third molars were disinfected in a solution of 10% formalin for 7 days and were then prepared to receive a ceramic crown. Impressions were made with polyvinyl siloxane and lithium disilicate pressed crowns made and cemented with 1 of 3 resin luting cements. The marginal discrepancy was measured at 4 points on the finishing line of each tooth, with optical microscopy at ×200 magnification before and after cementation. Statistical analysis was done with the Kruskal-Wallis test to compare the median marginal increase among the 3 groups (a=.05). RESULTS: The least amount of marginal increase after cementation was with Harvard PremiumFlow cement, with an average marginal increase of 42 ±11 μm. RelyX Ultimate cement increased the margins by an average 45 ±29 μm. The highest marginal increase was found in the Enamel Plus HRi preheated composite resin group (116 ±47 μm). CONCLUSIONS: The marginal increase of pressed crowns cemented with preheated composite resin (Enamel Plus HRi) exceeded the clinically acceptable range of marginal discrepancy.
Keywords: In Vitro Techniques; zubní korunky; Dental Porcelain; moláry; zubní porcelán; techniky in vitro; lidé; pryskyřičné cementy; Dental Cements; zubní cementy; Crowns; Resin Cements; Molar; Humans